2008
DOI: 10.1097/01.hp.0000310962.96089.44
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose to Surgical Staff From Positron-Emitter-Based Localization and Radiosurgery of Tumors

Abstract: Surgical tissue characterization based on radiotracer uptake has become much more common in recent years, particularly due to the advent of the sentinel lymph node biopsy technique. Radiolabeled pharmaceuticals are used with hand-held gamma-sensitive probes, which are capable of localizing small tumors and lymph nodes that are first identified via scintigraphy. The radiation safety of such radioguided procedures, which typically employ 99mTc, has been well established. Now, with the emergence of 18F-fluorodeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…The low radiation exposure to staff found in this study is in accordance with previously reported exposure levels from 18 F-FDG-guided breast surgery procedures (20,21) and comparable to the radiation dose reported for interventional cardiology procedures (1-50 mSv) (22). The number of 18 F-FDG CLIguided BCS procedures that could be performed in a routine clinical setting depends on the occupational limits on radiation exposure per country (Table 2).…”
Section: Discussionsupporting
confidence: 78%
“…The low radiation exposure to staff found in this study is in accordance with previously reported exposure levels from 18 F-FDG-guided breast surgery procedures (20,21) and comparable to the radiation dose reported for interventional cardiology procedures (1-50 mSv) (22). The number of 18 F-FDG CLIguided BCS procedures that could be performed in a routine clinical setting depends on the occupational limits on radiation exposure per country (Table 2).…”
Section: Discussionsupporting
confidence: 78%
“…Sensitivity and specificity of PET are relatively high for 18 F-FDG-avid breast tumors 100,101. However, because of limited spatial resolution of PET imaging, small tumors (<1 cm) are difficult to detect, whereas breast screening programs and technological developments have led to a considerable reduction in the size of breast cancers being detected 97,102,103.…”
Section: Future Directionsmentioning
confidence: 99%
“…Additionally, PET lacks specificity, because normal physiologic uptake of 18 F-FDG can be demonstrated to varying degrees in nonmalignant tissues, such as inflammatory tissue 91. Finally, PET has the disadvantage of high costs and radiation exposure to primary operating personnel during the intraoperative 18 F-FDG PET procedure is expected to be relatively high 101,102…”
Section: Future Directionsmentioning
confidence: 99%
“…Thus the utility in the context under discussion, nonpalpable lesions, is limited. Add to this the high costs and radiation exposure, and intra-operative PET remains largely an experimental tool [43,44].…”
Section: Discussionmentioning
confidence: 99%